Preparation method of high-conductivity nano bimetallic composite material
By clading copper strips on the outer layer of the aluminum alloy conductor core wire and preparing high-conductive nanobimetal composite materials, the problems of high resistivity and low current carrying capacity of aluminum alloy conductors are solved, and the conductive performance is close to that of pure copper wire is achieved, and it is suitable for a variety of electronic equipment.
Patent Information
- Application Number
- CN202411724361.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
With the same electrical properties, existing aluminum alloy conductors have insufficient resistivity, small current carrying capacity, and high heating temperature, making it difficult to replace copper conductors.
Nano-rare earth aluminum alloy material is used as the conductor core wire and the outer layer is coated with copper strips to make a highly conductive nanobimetal composite material by drawing. The components of the material include copper powder, silicon powder, barium, alpha-alumina, cerium oxide, yttrium oxide, solid glass beads and reinforcement agents.
The conductivity and physical properties are significantly improved, making the conductivity of the bimetal composite close to that of pure copper wire and reduce resistivity, and is suitable for cables, supercapacitors or chemical sensors and other fields.
Smart Images

Figure BDA0005158833310000091
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal composite materials, and in particular relates to a method for preparing a highly conductive nano bimetallic composite material. Background Art
[0002] With the continued rapid growth of China's economy and the continuous expansion of industries such as the power industry, data communications industry, and urban rail transit industry, the demand for conductive materials will also grow rapidly. Among them, copper, as an excellent conductor material, is widely used in the field of wires and cables due to its advantages such as large current carrying capacity, strong corrosion resistance, high strength, good thermal stability, and high machinability. As a country with a huge copper consumption, my country's copper resources are very scarce, and about 70% of copper is imported each year. Affected by the rising international copper prices, the cost of domestic power cables is also rising rapidly. Therefore, finding alternatives to copper wires and cables is becoming more and more important at a time when the international situation and resources are becoming increasingly tense.
[0003] In the middle of the 20th century, my country proposed the policy of "replacing copper with aluminum". Although the conductivity of aluminum conductors is close to that of copper conductors, aluminum has disadvantages such as low melting point, softness and poor mechanical strength, which makes aluminum core cables less reliable and prone to failure. Therefore, it is urgent to find a substitute for copper and aluminum cables.
[0004] Aluminum alloy is one of the important light metal materials. It is widely used in aerospace, aviation, automobile, transportation and other fields due to its good electrical conductivity, thermal conductivity, corrosion resistance, excellent mechanical properties and physical properties. The high-strength aluminum alloy materials commonly used in the automobile and weapons industries are mainly 2 series aluminum alloys, which have high tensile strength, toughness and fatigue strength, good heat resistance, processing and welding properties. Automobile pistons mainly use hypereutectic Al-Si alloys, which have low density and small linear expansion coefficient. Civilian aluminum alloys are mainly 5 series aluminum alloys and 6 series aluminum alloys. Because of their excellent strength, processability and corrosion resistance, they are widely used in shipbuilding, construction, transportation, electronic equipment and other fields.
[0005] Under the same electrical performance, compared with traditional copper conductors, aluminum alloy conductors have the advantages of light weight, low price, good ductility, etc. However, aluminum alloy still has shortcomings such as high resistivity, small current carrying capacity, and high heating temperature. Under the same cross-sectional area, the conductivity of aluminum alloy is 61.8% of the most commonly used reference material copper IACS, and the current carrying capacity is 79% of copper. Therefore, further reducing the resistivity of aluminum alloy has become an urgent matter. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a method for preparing a highly conductive nano bimetallic composite material to solve the technical problems mentioned in the above background technology.
[0007] In order to achieve the above object, the present invention provides a method for preparing a highly conductive nano bimetallic composite material using the following technical scheme:
[0008] A high-conductivity nano bimetallic composite material is prepared by drawing a nano rare earth aluminum alloy material as a conductor core wire and coating the outer layer of the conductor core wire with a layer of copper strip; the nano rare earth aluminum alloy material comprises the following components: 3-10% copper powder, 3-6% silicon powder, 0.5-5% barium, 0.5-2% α-alumina, 0.1-1% cerium oxide, 0.1-1% yttrium oxide, 0.1-1% solid glass microspheres, 0.1-0.5% reinforcing agent, and the balance is aluminum powder.
[0009] Preferably, the reinforcing agent is composed of modified montmorillonite, phenolic resin, Ag + And pyridine prepared.
[0010] Preferably, the reinforcing agent is prepared by the following steps:
[0011] (1) The rare earth material La(NO 3 ) 3 Completely dissolve in pure water, add montmorillonite and stir thoroughly, then add silver nitrate and continue to stir thoroughly, then add phenolic resin and continue to stir, filter, wash and calcine the filter cake;
[0012] (2) The calcined filter cake is completely dissolved in pure water, pyridine is added and heated to 90°C, polyamide polyamine epichlorohydrin oligomer is added, the mixture is stirred and reacted at the temperature, and then the filter cake is filtered and washed and fully dried at 100°C to obtain the product.
[0013] Preferably, the montmorillonite, La(NO 3 ) 3 The mass ratio of silver nitrate, pyridine, and polyamide polyamine epichlorohydrin oligomer is 100:5~10:1~5:10~20:1~5.
[0014] A method for preparing a highly conductive nano bimetallic composite material comprises the following steps:
[0015] (1) making an aluminum rod, making the nano rare earth aluminum alloy material into an aluminum rod;
[0016] (2) Copper cladding: using high-frequency welding technology, the copper strip is evenly and tightly wrapped around the aluminum rod to form a copper-clad aluminum structure;
[0017] (3) Drawing: The copper-clad aluminum structure is continuously drawn through a wire drawing machine to reduce the wire diameter to obtain a highly conductive nano bimetallic composite material.
[0018] Preferably, in step (1), the steps of making the aluminum rod from the nano rare earth aluminum alloy material are as follows:
[0019] S1. Dry the ball mill, aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass beads and reinforcing agent separately, put the weighed aluminum powder, copper powder, silicon powder, barium, cerium oxide, yttrium oxide, solid glass beads and reinforcing agent into the ball mill, with a ball-to-material ratio of 9:1, and operate the ball mill at a speed of 150-200 r / min in an argon atmosphere to obtain a premix;
[0020] S2, the premix and the co-solvent are charged into an internal mixer for melt blending at a blending temperature of 150 to 200° C. and a melt blending speed of 100 to 180 r / min rpm to obtain a blend;
[0021] S3, vulcanizing the above blend and ethyl formate using a flat vulcanizer at a temperature of 180-200° C. and a pressure of 8-10 MPa to obtain a vulcanized blend;
[0022] S4, forming the above-mentioned vulcanized blend into an aluminum rod through an extruder.
[0023] Preferably, the purity of the aluminum powder is ≥99% and the particle size is 100-200 meshes.
[0024] Preferably, the purity of copper powder, silicon powder, barium, α-alumina, cerium oxide, and yttrium oxide is ≥99%, and the particle size is 100-200 mesh.
[0025] Preferably, the co-solvent is calcium oxide, magnesium oxide or aluminum oxide; the mass ratio of the co-solvent to the premix is 0.1 to 5:100.
[0026] A highly conductive nano bimetallic composite material is used in cables, supercapacitors or chemical sensors.
[0027] Beneficial effects:
[0028] The present invention provides a method for preparing a high-conductivity nano bimetallic composite material. The present invention uses a nano rare earth aluminum alloy material as a conductor core wire, copper, silicon powder, barium, etc. are added to the conductor core wire, and α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and a reinforcing agent are added to increase the conductivity of the conductor core wire and enhance its performance, so that the bimetallic composite material has higher conductivity and excellent physical properties, and has a wider range of applications. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0030] Example 1
[0031] A high-conductivity nano bimetallic composite material, which is made of a nano rare earth aluminum alloy material as a conductor core wire, a layer of copper strip coated on the outer layer of the conductor core wire, and drawn; the components of the nano rare earth aluminum alloy material are as follows: 8% copper powder, 3% silicon powder, 0.5% barium, 0.5% α-alumina, 0.1% cerium oxide, 0.1% yttrium oxide, 0.1% solid glass microspheres, 0.1% reinforcing agent, and the balance is aluminum powder.
[0032] The reinforcing agent is composed of modified montmorillonite, phenolic resin, Ag + and pyridine, the specific steps are as follows:
[0033] (1) The rare earth material La(NO 3 ) 3 Completely dissolve in pure water, add montmorillonite and stir thoroughly, then add silver nitrate and continue to stir thoroughly, then add phenolic resin and continue to stir, filter, wash and calcine the filter cake;
[0034] (2) The calcined filter cake is completely dissolved in pure water, pyridine is added and heated to 90°C, polyamide polyamine epichlorohydrin oligomer is added, the mixture is stirred and reacted at the temperature, and then the filter cake is filtered and washed and fully dried at 100°C to obtain the product.
[0035] Among them, montmorillonite, La(NO 3 ) 3 The mass ratio of silver nitrate, pyridine, and polyamide polyamine epichlorohydrin oligomer is 100:10:5:20:5.
[0036] Example 2
[0037] A high-conductivity nano bimetallic composite material, which is made of a nano rare earth aluminum alloy material as a conductor core wire, a copper strip coated on the outer layer of the conductor core wire, and drawn; the components of the nano rare earth aluminum alloy material are as follows: 9% copper powder, 5% silicon powder, 3% barium, 1% α-alumina, 0.5% cerium oxide, 0.5% yttrium oxide, 0.5% solid glass microspheres, 0.3% reinforcing agent, and the balance is aluminum powder.
[0038] The reinforcing agent is composed of modified montmorillonite, phenolic resin, Ag + and pyridine, the specific steps are as follows:
[0039] (1) The rare earth material La(NO 3 ) 3 Completely dissolve in pure water, add montmorillonite and stir thoroughly, then add silver nitrate and continue to stir thoroughly, then add phenolic resin and continue to stir, filter, wash and calcine the filter cake;
[0040] (2) The calcined filter cake is completely dissolved in pure water, pyridine is added and heated to 90°C, polyamide polyamine epichlorohydrin oligomer is added, the mixture is stirred and reacted at the temperature, and then the filter cake is filtered and washed and fully dried at 100°C to obtain the product.
[0041] Among them, montmorillonite, La(NO 3 ) 3 The mass ratio of silver nitrate, pyridine, and polyamide polyamine epichlorohydrin oligomer is 100:5:1:10:1.
[0042] Example 3
[0043] A high-conductivity nano bimetallic composite material, which is made by drawing a nano rare earth aluminum alloy material as a conductor core wire, coating the outer layer of the conductor core wire with a layer of copper strip; the nano rare earth aluminum alloy material comprises the following components: 10% copper powder, 6% silicon powder, 5% barium, 2% α-alumina, 1% cerium oxide, 1% yttrium oxide, 1% solid glass microspheres, 0.5% reinforcing agent, and the balance is aluminum powder.
[0044] The reinforcing agent is composed of modified montmorillonite, phenolic resin, Ag + and pyridine, the specific steps are as follows:
[0045] (1) The rare earth material La(NO 3 ) 3 Completely dissolve in pure water, add montmorillonite and stir thoroughly, then add silver nitrate and continue to stir thoroughly, then add phenolic resin and continue to stir, filter, wash and calcine the filter cake;
[0046] (2) The calcined filter cake is completely dissolved in pure water, pyridine is added and heated to 90°C, polyamide polyamine epichlorohydrin oligomer is added, the mixture is stirred and reacted at the temperature, and then the filter cake is filtered and washed and fully dried at 100°C to obtain the product.
[0047] Among them, montmorillonite, La(NO 3 ) 3 The mass ratio of silver nitrate, pyridine, and polyamide polyamine epichlorohydrin oligomer is 100:8:3:15:3.
[0048] Example 4
[0049] A highly conductive nano bimetallic composite material, which is made of a nano rare earth aluminum alloy material as a conductor core wire, a layer of copper strip coated on the outer layer of the conductor core wire, and drawn; the components of the nano rare earth aluminum alloy material are as follows: 8% copper powder, 6% silicon powder, 3% barium, 2% α-alumina, 1% cerium oxide, 0.5% yttrium oxide, 0.7% solid glass microspheres, 0.5% reinforcing agent, and the balance is aluminum powder.
[0050] The reinforcing agent is composed of modified montmorillonite, phenolic resin, Ag + and pyridine, the specific steps are as follows:
[0051] (1) The rare earth material La(NO 3 ) 3 Completely dissolve in pure water, add montmorillonite and stir thoroughly, then add silver nitrate and continue to stir thoroughly, then add phenolic resin and continue to stir, filter, wash and calcine the filter cake;
[0052] (2) The calcined filter cake is completely dissolved in pure water, pyridine is added and heated to 90°C, polyamide polyamine epichlorohydrin oligomer is added, the mixture is stirred and reacted at the temperature, and then the filter cake is filtered and washed and fully dried at 100°C to obtain the product.
[0053] Among them, montmorillonite, La(NO 3 ) 3 The mass ratio of silver nitrate, pyridine, and polyamide polyamine epichlorohydrin oligomer is 100:8:5:20:4.
[0054] Example 5
[0055] A method for preparing a highly conductive nano bimetallic composite material comprises the following steps:
[0056] (1) making an aluminum rod, using the composition in Example 1 to make the nano rare earth aluminum alloy material into an aluminum rod;
[0057] (2) Copper cladding: using high-frequency welding technology, the copper strip is evenly and tightly wrapped around the aluminum rod to form a copper-clad aluminum structure;
[0058] (3) Drawing: The copper-clad aluminum structure is continuously drawn through a wire drawing machine to reduce the wire diameter to obtain a highly conductive nano bimetallic composite material.
[0059] In step (1), the steps of making the aluminum rod from the nano rare earth aluminum alloy material are as follows:
[0060] S1. Dry the ball mill, aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent separately, put the weighed aluminum powder, copper powder, silicon powder, barium, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent into the ball mill, with a ball-to-material ratio of 9:1, and operate the ball mill at a speed of 150r / min in an argon atmosphere to obtain a premix; the purity of the aluminum powder is ≥99%, and the particle size is 100-200 mesh; the purity of the copper powder, silicon powder, barium, α-alumina, cerium oxide, and yttrium oxide is ≥99%, and the particle size is 100-200 mesh. The aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent adopt the composition of Example 1.
[0061] S2. The premix and the cosolvent are placed in an internal mixer for melt blending at a blending temperature of 150° C. and a melt blending speed of 100 r / min rpm to obtain a blend. The cosolvent is calcium oxide, magnesium oxide or aluminum oxide; and the mass ratio of the cosolvent to the premix is 0.5:100.
[0062] S3, vulcanizing the above blend and ethyl formate using a flat vulcanizer at a temperature of 180° C. and a pressure of 8 MPa to obtain a vulcanized blend, wherein the mass ratio of the blend to ethyl formate is 1:100.
[0063] S4, heating the above-mentioned vulcanized blend to 710° C., pouring the molten aluminum alloy liquid into a mold to cool and solidify it, and then heating it to 500° C. and rolling it into an aluminum rod on a loop rolling mill.
[0064] Example 6
[0065] A method for preparing a highly conductive nano bimetallic composite material comprises the following steps:
[0066] Similar to Example 5, the steps of making the aluminum rod from the nano rare earth aluminum alloy material using the composition in Example 2 are as follows:
[0067] S1. Dry the ball mill, aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent separately, put the weighed aluminum powder, copper powder, silicon powder, barium, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent into the ball mill, with a ball-to-material ratio of 9:1, and operate the ball mill at a speed of 180r / min in an argon atmosphere to obtain a premix; the purity of the aluminum powder is ≥99%, and the particle size is 100-200 mesh; the purity of the copper powder, silicon powder, barium, α-alumina, cerium oxide, and yttrium oxide is ≥99%, and the particle size is 100-200 mesh. The aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent adopt the composition of Example 2.
[0068] S2. The premix and the cosolvent are placed in an internal mixer for melt blending at a blending temperature of 180°C and a melt blending speed of 150 r / minrpm to obtain a blend. The cosolvent is calcium oxide, magnesium oxide or aluminum oxide; and the mass ratio of the cosolvent to the premix is 3:100.
[0069] S3, vulcanizing the above blend and ethyl formate using a flat vulcanizer at a temperature of 190° C. and a pressure of 9 MPa to obtain a vulcanized blend, wherein the mass ratio of the blend to ethyl formate is 3:100.
[0070] S4, heating the above-mentioned vulcanized blend to 710°C, pouring the molten aluminum alloy liquid into a mold, cooling and solidifying it into a mold.
[0071] Example 7
[0072] A method for preparing a highly conductive nano bimetallic composite material comprises the following steps:
[0073] Similar to Example 5, the steps of making the aluminum rod from the nano rare earth aluminum alloy material using the composition in Example 3 are as follows:
[0074] S1. Dry the ball mill, aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent separately, put the weighed aluminum powder, copper powder, silicon powder, barium, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent into the ball mill, with a ball-to-material ratio of 9:1, and operate the ball mill at a speed of 200r / min in an argon atmosphere to obtain a premix; the purity of the aluminum powder is ≥99%, and the particle size is 100-200 mesh; the purity of the copper powder, silicon powder, barium, α-alumina, cerium oxide, and yttrium oxide is ≥99%, and the particle size is 100-200 mesh. The aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent adopt the composition of Example 3.
[0075] S2. The premix and the cosolvent are placed in an internal mixer for melt blending at a blending temperature of 200°C and a melt blending speed of 180 r / minrpm to obtain a blend. The cosolvent is calcium oxide, magnesium oxide or aluminum oxide; the mass ratio of the cosolvent to the premix is 100.
[0076] S3, vulcanizing the above blend and ethyl formate using a flat vulcanizer at a temperature of 200° C. and a pressure of 10 MPa to obtain a vulcanized blend. The mass ratio of the blend to ethyl formate is 5:100.
[0077] S4, heating the above-mentioned vulcanized blend to 710°C, pouring the molten aluminum alloy liquid into a mold, cooling and solidifying it into a mold.
[0078] Example 8
[0079] A method for preparing a highly conductive nano bimetallic composite material comprises the following steps:
[0080] Similar to Example 5, the steps of making the aluminum rod from the nano rare earth aluminum alloy material using the composition in Example 4 are as follows:
[0081] S1. Dry the ball mill, aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent separately, put the weighed aluminum powder, copper powder, silicon powder, barium, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent into the ball mill, with a ball-to-material ratio of 9:1, and operate the ball mill at a speed of 200r / min in an argon atmosphere to obtain a premix; the purity of the aluminum powder is ≥99%, and the particle size is 100-200 mesh; the purity of the copper powder, silicon powder, barium, α-alumina, cerium oxide, and yttrium oxide is ≥99%, and the particle size is 100-200 mesh. The aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and reinforcing agent adopt the composition of Example 1.
[0082] S2. The premix and the cosolvent are placed in an internal mixer for melt blending at a blending temperature of 200°C and a melt blending speed of 160 r / minrpm to obtain a blend. The cosolvent is calcium oxide, magnesium oxide or aluminum oxide; and the mass ratio of the cosolvent to the premix is 2:100.
[0083] S3, vulcanizing the above blend and ethyl formate using a flat vulcanizer at a temperature of 180° C. and a pressure of 9 MPa to obtain a vulcanized blend, wherein the mass ratio of the blend to ethyl formate is 2:100.
[0084] S4, heating the above-mentioned vulcanized blend to 710°C, pouring the molten aluminum alloy liquid into a mold, cooling and solidifying it into a mold.
[0085] Using the composition of the above-mentioned Example 1 and the method of Example 5, copper-clad aluminum of specifications of 10H, 15H and 20H were respectively manufactured, and their resistivity and conductivity were measured. The results are shown in the following table.
[0086] Table 1 Test results of bimetallic composite materials
[0087]
[0088] Among them, H represents the cross-sectional area ratio of copper, and 20H represents that the cross-sectional area ratio of copper is 20%.
[0089] It can be seen from Table 1 that the resistivity of copper-clad aluminum of 10H, 15H and 20H specifications is 0.02743Ω·mm 2 / m, 0.02676Ω·mm 2 / m and 0.02594Ω·mm 2 / m, much lower than 0.028Ω·mm of pure aluminum wire 2 / m, and the conductivity of copper-clad aluminum with specifications of 10H, 15H and 20H are 62.85, 64.42 and 66.46IACS of pure copper wire respectively. Its conductivity exceeds that of pure aluminum wire and it is the best new material to replace pure copper wire.
[0090] Due to their excellent electrical conductivity, bimetallic composites can be used as materials for cables, supercapacitors or chemical sensors.
[0091] The present invention provides a method for preparing a highly conductive nano bimetallic composite material. On the basis of aluminum, copper, silicon powder, barium and other metal materials with good conductive properties are added. At the same time, α-alumina, cerium oxide, yttrium oxide, solid glass microbeads and a reinforcing agent are added, and the mixture is mixed to prepare a bimetallic composite material. The conductivity of the bimetallic composite material is increased and the performance of the bimetallic composite material is enhanced, so that the bimetallic composite material has higher conductive properties and excellent physical properties, and has a wider range of applications.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A highly conductive nano bimetallic composite material, characterized in that: The composite material uses a nano rare earth aluminum alloy material as a conductor core wire, and a layer of copper strip is coated on the outer layer of the conductor core wire, and is obtained after drawing; the components of the nano rare earth aluminum alloy material are as follows: 3-10% copper powder, 3-6% silicon powder, 0.5-5% barium, 0.5-2% α-alumina, 0.1-1% cerium oxide, 0.1-1% yttrium oxide, 0.1-1% solid glass microbeads, 0.1-0.5% reinforcing agent, and the balance is aluminum powder.
2. The highly conductive nano bimetallic composite material according to claim 1, characterized in that: The reinforcing agent is composed of modified montmorillonite, phenolic resin, Ag + And pyridine prepared.
3. The highly conductive nano bimetallic composite material according to claim 2, characterized in that: The reinforcing agent is prepared by the following steps: (1) The rare earth substance La(NO3)3 is completely dissolved in pure water, montmorillonite is added and stirred thoroughly, silver nitrate is added and stirred thoroughly, and then phenolic resin is added and stirred thoroughly, filtered, washed and the filter cake is calcined; (2) The calcined filter cake is completely dissolved in pure water, pyridine is added and heated to 90°C, polyamide polyamine epichlorohydrin oligomer is added, the mixture is stirred and reacted at the temperature, and then the filter cake is filtered and washed and fully dried at 100°C to obtain the product.
4. The highly conductive nano bimetallic composite material according to claim 3, characterized in that: The mass ratio of the montmorillonite, La(NO3)3, silver nitrate, pyridine and polyamide polyamine epichlorohydrin oligomer is 100:5-10:1-5:10-20:1-5.
5. A method for preparing a highly conductive nano bimetallic composite material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: (1) making an aluminum rod, making the nano rare earth aluminum alloy material into an aluminum rod; (2) Copper cladding: using high-frequency welding technology, the copper strip is evenly and tightly wrapped around the aluminum rod to form a copper-clad aluminum structure; (3) Drawing: The copper-clad aluminum structure is continuously drawn through a wire drawing machine to reduce the wire diameter to obtain a highly conductive nano bimetallic composite material.
6. The method for preparing the highly conductive nano bimetallic composite material according to claim 5, characterized in that: In step (1), the steps of making the aluminum rod from the nano rare earth aluminum alloy material are as follows: S1. Dry the ball mill, aluminum powder, copper powder, silicon powder, barium, α-alumina, cerium oxide, yttrium oxide, solid glass beads and reinforcing agent separately, put the weighed aluminum powder, copper powder, silicon powder, barium, cerium oxide, yttrium oxide, solid glass beads and reinforcing agent into the ball mill, with a ball-to-material ratio of 9:1, and operate the ball mill at a speed of 150-200 r / min in an argon atmosphere to obtain a premix; S2, the premix and the co-solvent are charged into an internal mixer for melt blending at a blending temperature of 150 to 200° C. and a melt blending speed of 100 to 180 r / min rpm to obtain a blend; S3, vulcanizing the above blend and ethyl formate using a flat vulcanizer at a temperature of 180-200° C. and a pressure of 8-10 MPa to obtain a vulcanized blend; S4, heating the above-mentioned vulcanized blend to 710°C, pouring the molten aluminum alloy liquid into a mold, cooling and solidifying it into a mold.
7. The method for preparing the highly conductive nano bimetallic composite material according to claim 6, characterized in that: The purity of the aluminum powder is ≥99%, and the particle size is 100-200 meshes.
8. The method for preparing the highly conductive nano bimetallic composite material according to claim 6, characterized in that: The purity of copper powder, silicon powder, barium, α-alumina, cerium oxide and yttrium oxide is ≥99%, and the particle size is 100-200 meshes.
9. The method for preparing the highly conductive nano bimetallic composite material according to claim 6, characterized in that: The co-solvent is calcium oxide, magnesium oxide or aluminum oxide; the mass ratio of the co-solvent to the premix is 0.1-5:
100.
10. Use of the highly conductive nano bimetallic composite material according to any one of claims 1 to 4 in cables, supercapacitors or chemical sensors.